Characteristics, Treatment, and Long-Term Outcome of Gastrointestinal Involvement in Behcet's Syndrome: A Strobe-Compliant Observational Study From a Dedicated Multidisciplinary Center. Issue 16 (April 2016) - Hatemi, Ibrahim; Esatoglu, Sinem Nihal; Hatemi, Gulen; Erzin, Yusuf; Yazici, Hasan; Celik, Aykut Ferhat
Abstract : Abstract: Gastrointestinal involvement is rare in Behçet's syndrome (BS) patients from the Mediterranean basin. We report the demographic and disease characteristics, treatment modalities, and outcome of patients with gastrointestinal involvement in BS (GIBS). We retrospectively reviewed the charts of all BS patients in our BS clinic with a diagnosis of GIBS. Patients were invited to the clinic to assess their outcome. Among 8763 BS patients, we identified 60 with GIBS (M/F: 32/28, mean age at diagnosis: 34 ± 10, mean follow-up: 7.5 ± 4 years), after excluding 22 patients with mimicking symptoms. Six (10%) had juvenile-onset BS. The most common intestinal localization was ileocecal region (36/59, 61%) mainly as big oval ulcer/s. Initial treatment was azathioprine for moderate to severe (n = 37) and 5-ASA for mild cases (n = 16). Anti-TNFs and/or thalidomide provided remission in 12 of 18 (67%) refractory patients. Emergency surgery was required in 22 patients. Nine patients did not receive postoperative immunomodulators and 8 relapsed. Overall, 48 of 60 (80%) patients were in remission (29/48 without treatment) at the time of survey. Three recently treated and 2 refractory patients were still active, 3 had died due to non-GI-related reasons, and 4 were lost to follow-up. Careful evaluation for excluding mimickers is important during the diagnosis of GIBS. Azathioprine seems to be a good choice as first-line treatment with high remission rates and few adverse events. Thalidomide and/or TNF-alpha antagonists may be preferred in resistant cases. Surgery may be required for perforations or massive bleeding, and postoperative immunosuppressive treatment is necessary for preventing postoperative recurrences.